Dancing with the (un)seen: Problematizing the viewer’s gaze through Mediterraneo’s visual aesthetics - Vari, Silvia (Mediascapes journal, 2023)
Since the 1990s, international migration has become one of the most pressing socio-political issues in Italy. Subsequently, the topic of undocumented immigration has gained increased visibility in Italian society, making the infamous images of incoming masses of migrants ever more frequent in the mainstream media. At the same time, since the turn of the new millennium and thanks to the enhanced diffusion of the graphic novel format, significant changes also occurred in the Italian comics scene at the start of the 21st century. The fumetto di realtà [non-fiction comics] saw a consistent rise in popularity, exemplified by the proliferation of autobiographical comics and graphic reportages focusing attention on both personal experiences and socio-political events. Comics and graphic novels have started addressing the topical events of the present, including the phenomenon of immigration towards Italy from the Mediterranean basin. This study aims at exploring the peculiarities of graphic narratives in portraying experiences of forced migration, by paying particular attention to the specific framing strategies of the medium and the political affordances therein. Through the close reading of the wordless graphic novel Mediterraneo (2018), the present contribution analyzes how the inherent problematization of notions of presence and absence in comics' spatial and visual grammar can constitute a call for the active participation of viewers in the narrative, potentially mobilizing the Rancièrian formulation of spectators’ emancipation that eschews the long-standing association of viewing with inertia.